Effects of Nitrate Supplementation on Cardiovascular and Autonomic Reactivity in African-American Females. (23rd February 2014) - Bond, Vernon; Curry, Bryan H.; Adams, R. George; Asadi, M. Sadegh; Stancil, Kimani A.; Millis, Richard M.; Haddad, Georges E.
Abstract : Previous studies have shown that beetroot juice (BJ) decreases systolic blood pressure (SBP) and oxygen demand. This study tests the hypothesis that a beetroot juice (BJ) treatment increases heart rate variability (HRV) measured by the average standard deviation of normal-normal electrocardiogram RR intervals (SDNN) and the low frequency (LF), mainly sympathetic, fast Fourier transform spectral index of HRV. The subjects were 13 healthy young adult African-American females. Placebo control orange juice (OJ) and BJ treatments were given on separate days. Blood nitric oxide [NO], SBP and RR intervals were measured at rest and at constant workloads set to 40% and 80% of the predeterminedVO 2 peak . Two hours after ingestion the BJ treatment increased [NO] and decreased SBP. BJ also increased SDNN at rest and at the 40%VO 2 peak workload, without significant effects on LF. SDNN was significantly greater after the BJ than after the OJ treatment, across the two physical activity conditions and SDNN was (negatively) correlated with SBP. These results suggest that BJ decreases SBP and increases HRV at rest and during aerobic exercise. Similar results in subjects with prehypertension or hypertension could translate to a dietary nitrate treatment for hypertension.